Setting guidelines for "an administrative support" to carry out extension education program at the School of Agronomy of the Federal University of Ceará - Brazil - Sousa Filho, Antônio de Albuquerque (1972)
The extension function within EAUFC is felt today as a necessary activity to be carried out. However, there are obstacles in doing it. Among others, the writer of this study feels that an adequate administrative support (understood here in a broad sense) is the key factor. Because of this, some administrative guidelines necessary to improve administrative support in order to help those Extension programs within EAUFC have been considered here. In order to have a better understanding of adequate functions and administrative support to carry out the extension function within Brazilian higher educational institutions, and consequently within EAUFC, some bibliographical material was reviewed. This bibliography was related to the roles of colleges of agriculture and universities in developing countries, which involves economic, social and cultural elements and the intensity within each one; what is general and agricultural extension in terms of different philosophy, approaches used and correlations between them; administrative support to carry out the extension function based on administrative principles and techniques.